The Strategy for Constructing the Structure: Pt-O-Ce3+ Applied in Efficient NOx Removal - Liu, Guoquan; Hao, Zhifei; Mi, Xueyue; Ma, Nan; Zhang, He; Li, Yi; Zhan, Sihui (Frontiers in Environmental Chemistry, 2021)
Exploring a unique structure with superior catalytic performance remained a severe challenge in many important catalytic reactions. Here we reported a phenomenon that CeO2-based catalysts loading with different Pt precursors performed significant difference in the reduction of NO with H2. The supported platinum nitrate (PtCe(N)) exhibited a superior low-temperature catalytic performance than the supported chloroplatinic acid (PtCe(C)). In a wide operating temperature (125-200°С), more than 80% NOx conversion was achieved over PtCe(N), as well as excellent thermal stability. Various characterizations were used to study the microstructure and chemical electronic states. Results showed the introduction of low valence state of Pt species into the CeO2 resulted in the rearrangement of charges on the surface of CeO2, accompanied with increasing contents of oxygen vacancies and Ce3+ sites. Furthermore, the X-ray photoelectron spectroscopy (XPS) and Raman spectra confirmed that the divalent Pt atom could substitute Ce atom to form the Pt-O-Ce3+ structure, which was the base unit in the high-performance PtCe(N) catalyst. The tunable catalytic system of Pt-O-Ce3+ structure provides a strategy to design supported metal catalysts and may as model unit for future studies of many other reactions.